Collaborative authoring using wiki: An open education case study - Neill, James (International Journal for Students as Partners, 2024)
This case study describes a collaborative online authoring project in which undergraduate students co-produce open educational resources as a learning and assessment exercise. Over 1,500 chapters and videos about how psychological science can improve people’s motivational and emotional lives have been co-created. Wikiversity provides a simple and powerful open editing and hosting platform. The project’s key pedagogical principles include students as partners, open education, guided experiential learning, and self-determined learning. Other key ingredients include scaffolding, skill development, and formative feedback. Potential issues are framed as educational opportunities, including privacy and anonymity, intellectual property and copyright, and individual versus collective work. Collaborative online authoring projects offer real-world benefits over disposable essays in higher education. The principles and methods are adaptable to a wide variety of disciplines and educational contexts, offering a scalable approach to collaborative student-staff partnerships.